Stability analysis of nonthermal fixed points in longitudinally expanding kinetic theory - Mikheev, Aleksandr N.; Mazeliauskas, Aleksas; Berges, Jürgen (Physical review, 2022)
We use the Hamiltonian formulation of kinetic theory to perform a stability analysis of nonthermal fixed points in a non-Abelian plasma. We construct a perturbative expansion of the Fokker-Planck collision kernel in an adiabatic approximation and show that the (next-to-)leading order solutions reproduce the known nonthermal fixed point scaling exponents. Working at next-to-leading order, we derive the stability equations for scaling exponents and find the relaxation rate to the nonthermal fixed point. This approach provides the basis for an understanding of the prescaling phenomena observed in QCD kinetic theory and nonrelativistic Bose gas systems.
Gesehen am 23.08.2022